Strategies to optimize allocation of limited nutrients to sandy soils of the Sahel: A case study from Niger, West Africa - Gandah, M.; Bouma, Jetske; Brouwer, J.; Hiernaux, Pierre H.Y.; Duivenbooden, N. van (Elsevier, 2003)
Soils used for rainfed cereal production in Niger are sandy, deficient in major nutrients (N and P), and also low in organic matter content. Scarce rainfall with an unpredictable distribution in space and time makes crop and nutrient management difficult. Observations were made in 1996 and 1997 on management by a Fulani tribal household, based on manure application through corralling and on use of fallow. Field corralling of cattle left between 1.5 and 17Mgha-1 of manure on limited areas of the fields. Millet grain yields were increased from 500kgha-1 in areas manured 6 or more years ago to 1100kgha-1 in recently manured areas. Drought during the growing season of 1997 limited the effects of manure application on grain and straw yields. Soil carbon and nitrogen levels were higher at depths below 0.20m in sites where manure was applied 4-5 years ago (M4), while pH and P were higher in 0-0.10m of the soil profile in practices where manure was applied the same year (M0). Nutrient management in 1997 could have been improved by reducing the locally very high manure rates in order to fertilize a two or three times larger area and consequently improve yields over a larger area and reduce risks of nutrient leaching and crop damage from droughts.